2013
DOI: 10.1002/hbm.22365
|View full text |Cite
|
Sign up to set email alerts
|

Real world navigation independence in the early blind correlates with differential brain activity associated with virtual navigation

Abstract: Navigating is a complex cognitive task that places high demands on spatial abilities, particularly in the absence of sight. Significant advances have been made in identifying the neural correlates associated with various aspects of this skill, however, how the brain is able to navigate in the absence of visual experience remains poorly understood. Furthermore, how neural network activity relates to the wide variability in navigational independence and skill in the blind population is also unknown. Using fMRI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…In line with previous research in sighted MTLE patients and congenitally blind individuals without MTLE (Avila et al, 2006;Halko et al, 2014;Janszky et al, 2005;Jokeit et al, 2001;Kupers et al, 2010;Schacher et al, 2006), the present findings clearly show that nonvisual spatial navigation is suitable for mapping mesial temporal regions despite the co-occurrence of MTLE and congenital blindness. The recall of spatial episodic memories was associated with a rightward asymmetry of the mesial temporal lobes, referring to the presence of functional deficits adjacent to the epileptogenic lesion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous research in sighted MTLE patients and congenitally blind individuals without MTLE (Avila et al, 2006;Halko et al, 2014;Janszky et al, 2005;Jokeit et al, 2001;Kupers et al, 2010;Schacher et al, 2006), the present findings clearly show that nonvisual spatial navigation is suitable for mapping mesial temporal regions despite the co-occurrence of MTLE and congenital blindness. The recall of spatial episodic memories was associated with a rightward asymmetry of the mesial temporal lobes, referring to the presence of functional deficits adjacent to the epileptogenic lesion.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, language-related (inferior frontal and middle temporal gyri, pre-SMA, cerebellum), secondary motor, and visual association (inferior temporal gyrus) areas were activated. Consistent with previous research on spatial cognition and navigation in both sighted and congenitally blind individuals (Cattaneo et al, 2008;Halko et al, 2014;Kupers et al, 2010;Struiksma et al, 2009), this activity pattern strongly suggests that the patient recruited linguistic, motor, and nonvisual sensory sources during spatial navigation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Sound-based VEs have been investigated and developed for people who are blind (Halko, Connors, Sánchez, & Merabet, 2014; Gonzalez-Mora, 2003; Seki & Sato, 2011); however, this research showed that successful exploration using only sound requires a very high level of attention. “Haptics,” which refers to sensing and manipulation through touch, is another modality for interacting with a VE that can provide the user with tactile, kinesthetic, and reaction force information about the environment, as well as a means of controlling events in the VE.…”
Section: Introductionmentioning
confidence: 99%
“…The SBSoD is a widely used self‐report measure of environmental spatial ability that has been shown to correlate with performance on tests of the ability to update one's position and orientation in space (Arnold et al, ; Hegarty et al, ). The SBSoD is increasingly being used as a measure of overall spatial navigation ability—especially in MRI studies (Auger, Mullally, & Maguire, ; Epstein, Higgins, & Thompson‐Schill, ; Halko, Connors, Sánchez, & Merabet, ; Kong et al, ; Sulpizio et al, ; Wegman & Janzen, ). The scale is composed of 15 questions to which participants respond on a Likert‐type scale of 1–7 (strongly agree‐strongly disagree).…”
Section: Methodsmentioning
confidence: 99%